Implementasi Aplikasi “KONSELO” sebagai Multi-Platform Konseling Online Berbasis Sustainable Development Goals (SDGs) untuk Mereduksi Stres Akademik Mahasiswa bagi Konselor Perguruan Tinggi Negeri di Sumatera Barat - Ardi, Zadrian; Jasril, Ilmiyati Rahmy; Yendi, Frischa Meivilona; Adlya, Soeci Izzati; Putra, Ade Herdian; Guspriadi, Yan (Universitas Negeri Padang, 2023)
Academic stress can interfere with students studying in college. One effort that can be made to help students overcome academic stress is through online counseling services. Online counseling can be carried out effectively and efficiently if complete and adequate features support it. KONSELO is a product that we developed to meet the effectiveness and efficiency of implementing online counseling. To improve counselors' abilities in using the KONSELO application, Community Service activities are carried out through workshops and assistance in using KONSELO. Counselors who can operate the KONSELO application can use KONSELO as support for implementing counseling services in higher education to help students overcome academic stress.